Structural change and industrialization in the 1980s and 1990: The case in Malaysian manufacturing sector - Alias, Mohammad; Zainol, Azrae; Aziz, Norzilah; Che Mat, Siti Hadijah (2000)
The paper examines the process of structural change experienced by the Malaysian economy in general, and in particular the manufacturing sector, during the 1980s and 1990s.The study is motivated by the fact that the economy had experienced a remarkable process of structural change during the last two decades. The early 1980s witnessed the start of heavy industrialization and a second round of import substitution following a successful export oriented industrialization strategy implemented from the beginning of the 1970s. Structural change will be examined in the following ways.Firstly we will look at the relative contributions of the various economic sector, in particular the manufacturing sector, to the Gross Domestic Product (GDP).In addition, we will also look the structure of export, and the components of final demand expenditures. Secondly, we will employ econometric methodology to test for structural change in the manufacturing sector during the study period.A production function of the Cobb-Douglas type is estimated for the Malaysian manufacturing sector.The supply side of the sector is represented by a production function over a cross section of the manufacturing sector (28 industries at three digit levels).Suppose that there is an annual production function for the sector.Structural change of the sector will be reflected in the estimated parameters: the estimated production elasticities would be estimated differently for each year.This methodology has been employed production elasticities would be estimated differently for each year.This methodology has been employed by Yokoyama (1991)in his study of structural change of the Malaysian manufacturing sector in the 1980s.